USING A NEW MATHEMATICAL TECHNIQUE TO FIND NORMAL CURVATURE ON SMOOTH SURFACES IN CYLINDRICAL SYSTEM - RAHMAN ABDEL GADIR ABDEL RAHMAN, ABDEL RADI ABDEL; ALTAYB ALSAMANI, EMAN FARAH; MOHAMMED HAROUN, NEAMA YAHIA (International Journal For Research In Mathematics And Statistics, 2023)
We have dealt with some aspects of curvature and normal curvature. The purpose of this research is to find the normal curvature numerically in the cylindrical coordinate system using Matlab. Matlab is an interactive working environment that allows users to perform fairly complex computational tasks using only a few commands. We followed the Applied Mathematical method using a new mathematical technique (Matlab) and we found that finding the normal curvature in a cylindrical coordinate system using a new mathematical technique is more accurate and faster than numerical finding.